Antibacterial Efficacy of Silver Diamine Fluoride and 3M ESPE ClinproTM Tooth Crème Against Streptococcus mutans: A Comparative in vitro study - Shri Kavya, Anand; Amitha, H Anand; Aniyoor, Sanjana; Prabha, M Sandhya; Shetty, Nidhi J (International Journal of Dental Materials, 2025)
Background: Remineralizing agents such as Silver Diamine Fluoride (SDF) and 3M ESPETM Clinpro Tooth Crème have gained attention for their potential antimicrobial and enamel-strengthening properties. While fluoride-based therapies are widely used, there is limited comparative data on the antimicrobial efficacy of these agents. Aim: To evaluate and compare the antimicrobial effects of remineralizing agents in inhibiting S. mutans growth. Materials and methods: This in vitro study was conducted following ethical approval. The study involved 56 samples divided into four groups: Group I (SDF), Group II (3M ESPETM Clinpro Tooth Crème), Group III (2% Chlorhexidine - Positive Control), and Group IV (Distilled Water - Negative Control). The antimicrobial efficacy of each agent was evaluated using the Agar well diffusion method, with the Zone of Inhibition (ZOI) measured in millimetres. Statistical analysis was performed to determine the significance of differences between the groups. Results: The results demonstrated that SDF exhibited the highest antimicrobial efficacy, with a significantly larger zone of inhibition compared to 3M ESPETM Clinpro Tooth Crème. Conclusion: The findings suggest that SDF is more effective in bacterial inhibition compared to 3M ESPETM Clinpro Tooth Crème. The dual action of remineralization and antimicrobial activity highlights SDF as a promising agent for caries prevention and management. Further in vivo studies are required to validate these results in clinical settings.